Nuclear Magnetic Resonance Study on Microstructure and Permeability of Coals of Different Ranks - Jiajia Liu; Jianmin Hu; Gaini Jia; Jianliang Gao; Dan Wang (Advances in Civil Engineering)
The microscopic pore development of most coal seams in China leads to different permeability of coal seams and different gas drainage efficiency. Representative three coal rank coal samples were selected for saturation-centrifugation observation. The microscopic pore characteristics of coal samples were measured by nuclear magnetic resonance and liquid nitrogen adsorption methods. The experimental results showed that the coal samples were subjected to saturation-centrifugation and nuclear magnetic resonance (NMR) tests. It was found that the pores of the low-rank coal (XJ-1, XJ-2) were developed at various stages, and the connectivity between the pores was good and the permeability was also good. The adsorption pores of the intermediate coal (HB-1, HB-2) and high-rank coal (ZM-1, ZM-2) were relatively developed, and the connectivity between the pores was slightly poor. The parallel coal seam samples of coals of different ranks were better than the vertical bedding. The adsorption of liquid nitrogen showed that the low-order coal had more open pores and good gas permeability; the high-order coal had more openings at one end, more ink bottles, and narrow holes, and the gas permeability was not good. Studying the micropore structure and permeability of coals of different ranks has guiding significance for mastering the law of coal seam gas storage and transportation, extracting drilling arrangements, and increasing gas drainage and reducing greenhouse effect.